Insuring America's health : principles and recommendations (National Academies Press, 2004)
The lack of health insurance for tens of millions of Americans has serious negative consequences and economic costs not only for the uninsured themselves but also for their families, the communities they live in, and the whole country. The Committe urges Congress and the Administration to act immediately to eliminate this longstanding problem.
Keywords: Health insurance -- Government policy -- United States.; Medical policy -- United States.; Health services accessibility -- Government policy -- United States.; Health services accessibility.; Medical policy.; Medically uninsured persons.; Health insurance -- United States.; Health services accessibility -- United States.; Insurance, Health; Health Services Accessibility; Health Policy; Medically Uninsured; National Health Insurance, United States; United States; Assurance-maladie -- États-Unis.; Services de santé -- Accessibilité -- États-Unis.; Politique sanitaire -- États-Unis.; Services de santé -- Accessibilité -- Politique gouvernementale -- États-Unis.; Assurance-maladie.; Services de santé -- Accessibilité.; Politique sanitaire.; Personnes non assurées (Assurance-maladie); BUSINESS & ECONOMICS -- Insurance -- Health.; Medically uninsured persons; Health services accessibility; Health insurance; Health insurance -- Government policy; Health services accessibility -- Government policy; Medical policy; Krankenversicherung; USA; Couverture d'assurance.; Service de santé; Politique de la santé; Accès aux soins de santé; États-Unis.; Krankenversicherung.; USA.; Fulltext.; Government Publications, Federal.; Index not Present.; Internet Resources.